THE EFFECT OF RECYCLED POLYPROPYLENE AND CALCIUM CARBONATE ADDITION ON MECHANICAL PROPERTIES OF POLYPROPYLENE YARN - Heni Fitri Astuti; Muh Wahyu Sya’bani (Politek ATK Yogyakarta Press, 2024)
The use of recycled polypropylene can reduce the problem of plastic waste while lowering production costs. Likewise, the addition of calcium carbonate as a filler also reduces costs and influencing the mechanical characteristics of the plastic. However, this effort needs to consider the quality of the final product. This study aims to evaluate the effect of using recycled polypropylene and calcium carbonate on the mechanical characteristics of plastic yarn. Samples with PP : rPP : CaCO3 compositions of 100:0:0, 80:20:0, and 60:20:20 were used as comparisons. Each sample was processed and molded using an extruder machine and the resulting yarn was tested for tensile strength, elongation at break, and tenacity. The mechanical testing value was further confirmed using FTIR spectroscopy analysis. The research results showed that the FTIR spectra between virgin (PP) and recycled polypropylene (rPP) were similar. The tensile strength, elongation at break, and tenacity values ​​of virgin polypropylene are 3.40 kg/mm2, 27.25%, and 5.70 kgf. The addition of 20% RPP shows a decrease in value to 3.10 kg/mm2, 23.60%, and 4.60 kgf due to the presence of parts that were degraded during reprocessing. Meanwhile, the addition of 20% calcium carbonate also provided lower mechanical test results of 2.65 kg/mm2, 22.50%, and 4.25 kgf due to the difficulties of distribution and dispersion of the filler in the polymer matrix.